2015
DOI: 10.1016/j.sab.2014.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Non-spectral interferences due to the presence of sulfuric acid in inductively coupled plasma mass spectrometry

Abstract: Results of a systematic study concerning non-spectral interferences from sulfuric acid containing matrices on a large number of elements in inductively coupled plasma -mass spectrometry (ICP-MS)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(34 citation statements)
references
References 28 publications
1
33
0
Order By: Relevance
“…minimum energy defect of the reaction and conservation of the electron spin) and, as a consequence, non-argon based charge transfer reactions only affect certain elements [11,12]. It was found that As, P, Se and Te signals in ICP-MS are selectively enhanced by carbon and sulfur-based charge transfer reactions whereas Au, Hg, I, and Sb are only enhanced by carbon.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
See 3 more Smart Citations
“…minimum energy defect of the reaction and conservation of the electron spin) and, as a consequence, non-argon based charge transfer reactions only affect certain elements [11,12]. It was found that As, P, Se and Te signals in ICP-MS are selectively enhanced by carbon and sulfur-based charge transfer reactions whereas Au, Hg, I, and Sb are only enhanced by carbon.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…It is well-known that sulfuric and phosphoric acid solutions afford lower analyte transport rate values when compared to nitric acid solutions and, hence, lower signals are expected for these matrices [12,26]. Plasma energetic characteristics were not significantly modified by sulfur and phosphorus when compared to 1% w w -1 nitric acid solution.…”
mentioning
confidence: 94%
See 2 more Smart Citations
“…Such interferences may result from doublecharged or cluster ions. The former only slightly but the latter strongly depend on the plasma parameters [19,[21][22][23] …”
Section: Principles Of Analysis By Icp-msmentioning
confidence: 99%